2002
DOI: 10.1021/jf010958t
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive Effect of Green and Roasted Coffee on Streptococcus mutans' Adhesive Properties on Saliva-Coated Hydroxyapatite Beads

Abstract: Green and roasted coffees of the two most used species, Coffea arabica and Coffea robusta, several commercial coffee samples, and known coffee components were analyzed for their ability to interfere with Streptococcus mutans' sucrose-independent adsorption to saliva-coated hydroxyapatite (HA) beads. All coffee solutions showed high antiadhesive properties. The inhibition of S. mutans' adsorption to HA beads was observed both when coffee was present in the adsorption mixture and when it was used to pretreat the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 21 publications
2
75
1
8
Order By: Relevance
“…However, Herald and Davidson (1983) demonstrated a reduction in viable S. aureus at pH 5.0 by p-coumeric acid. No inhibition against Streptococcus mutans has been observed with caffeine (Daglia et al, 2002), indicating caffeine was not contributing to activity observed by Kubo et al (1993). Several of the flavonols found in yerba mate have also been examined for their antimicrobial activity-kaempferol, quercetin, and rutin (Panizzi et al, 2002;Rauha et al, 2000).…”
Section: Bioactive Properties and Health Implications Antimicrobial Amentioning
confidence: 99%
“…However, Herald and Davidson (1983) demonstrated a reduction in viable S. aureus at pH 5.0 by p-coumeric acid. No inhibition against Streptococcus mutans has been observed with caffeine (Daglia et al, 2002), indicating caffeine was not contributing to activity observed by Kubo et al (1993). Several of the flavonols found in yerba mate have also been examined for their antimicrobial activity-kaempferol, quercetin, and rutin (Panizzi et al, 2002;Rauha et al, 2000).…”
Section: Bioactive Properties and Health Implications Antimicrobial Amentioning
confidence: 99%
“…Coffea arabica and Coffea canephora extracts inhibit the adhesion of this pathogen to the surface of saliva-coated hydroxyapatite. The components with the highest antiadhesive activity in the coffee content are trigonelline, caffeine and chlorogenic acid [10].…”
Section: Coffeementioning
confidence: 99%
“…Stecchini and co-workers (1991) demonstrated that unlike A.hydrophila, Salmonella strains were resistant to glucoseglycine MRP products when products were generated at pH 6.0 and 8.8, thus revealing that subtle differences in MR chemical pathways was a factor. Daglia and co-workers [16] reported that Gram-positive bacteria were relatively more sensitive to MRP derived inhibition, compared to Gram-negative bacteria. Aminoreductone (AR), one of the early-stage Maillard reaction products often demonstrated in MRmodel was a antimicrobial component with activity in methicillinresistant Staphylococcus aureus [40].…”
Section: Factors Regulating Antimicrobial Efficacy Of Mrpsmentioning
confidence: 99%
“…Thus, it appears that melanoidin chromosphores are not totally responsible for antimicrobial activity [12]. Daglia and co-workers [16], evaluated the effect of coffee variety, degree of roasting and differences in brewing procedures on the inhibitory effect of coffee MRPs against both Grampositive and Gram-negative bacteria. The degree of roasting had a significant effect on antibacterial activity of MRPs.…”
Section: Factors Regulating Antimicrobial Efficacy Of Mrpsmentioning
confidence: 99%
See 1 more Smart Citation